2019
DOI: 10.3390/met9060647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Ring Rolling on the Wear Resistance of GCr15 Bearing Steel after Quenching and Tempering

Abstract: In this work, the effects on dry wear behavior of cold ring rolling (CRR) of GCr15 bearing steel, after quenching and tempering (QT) heat treatment are investigated. The effects on steel microstructures and wear mechanisms of CRR with different austenitizing times are also discussed. The results show that, with a short austenitizing time of 10 min, CRR can increase the retained austenite content, decrease the undissolved carbide content and improve the hardness of the specimen, thus reducing ploughing and fati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…Previous experiments have confirmed the significant effect of cold ring rolling on the microstructural evolution of GCr15 bearing steel during quenching and tempering [23]. The main reason for this effect is that the deformed initial microstructures lead to the refinement of austenite grains and the accelerated dissolution of carbides in the subsequent austenitization step [24], thus affecting the microstructure transformation during quenching and tempering [25,26].…”
Section: Introductionmentioning
confidence: 82%
“…Previous experiments have confirmed the significant effect of cold ring rolling on the microstructural evolution of GCr15 bearing steel during quenching and tempering [23]. The main reason for this effect is that the deformed initial microstructures lead to the refinement of austenite grains and the accelerated dissolution of carbides in the subsequent austenitization step [24], thus affecting the microstructure transformation during quenching and tempering [25,26].…”
Section: Introductionmentioning
confidence: 82%
“…AISI 52100 steel has high hardness, high strength, good wear resistance and high contact fatigue strength after quenching and tempering. Because of its good performance, it is often used to manufacture molds and precision measuring tools [ [1] , [2] , [3] , [4] ]. AISI 52100 steel is one of the most widely used materials in the field of bearin, however, after traditional heat treatment, the transformation of retained austenite to untempered martensite will occur in the process of long-term service of AISI 52100 steel, resulting in problems such as reduced hardness, loss of precision and decreased fatigue life [ [5] , [6] , [7] ].…”
Section: Introductionmentioning
confidence: 99%
“…They proposed that an increase in deformation degree led to the improvement of thermal stability and mechanical stability of residual austenite,which further improved wear resistance. Lu et al [17], proposed that cold rolling deformation reduced the size of grains and undissolved carbides after quenching and tempering, resulting in an increase in matrix hardness. In addition, Li et al [18], found that 30% of cold deformation significantly refined the previous austenite grains, thus improving the impact toughness of the martensitic microstructure.…”
Section: Introductionmentioning
confidence: 99%